Green synthesis of zinc oxide nanoparticles from Wodyetia bifurcata fruit peel extract: multifaceted potential in wound healing, antimicrobial, antioxidant, and anticancer applications - Moalwi, Adel; Kamat, Keerti; Muddapur, Uday M.; Aldoah, Bader; AlWadai, Hajar Hassan; Alamri, Abdulrahman Manaa; Alrashid, Fauwaz Fahad; Alsareii, Saeed Ali; Mahnashi, Mater H.; Shaikh, Ibrahim Ahmed; Khan, Aejaz Abdullatif; More, Sunil S. (Frontiers in Pharmacology, 2024)
This study focuses on the synthesis, characterization, and use of zinc oxide nanoparticles (ZnONPs) derived from Wodyetia bifurcatabifurcatae (W. bifurcatae) (Foxtail palm) fruit peel extract. ZnONPs are frequently synthesized utilizing a green technique that is both costeffective and ecologically friendly. ZnONPs were characterized utilizing analytical techniques.UVUltra Violet visible (UV-Vis) visible spectra showed peaks at 364 nm, confirming the production of ZnONPs. SEM analysis indicated that the nanoparticles generated were spherical/agglomerated, with diameters ranging from 11 to 25 nm. FTIR spectroscopy was used to identify the particular functional groups responsible for the nanoparticles' reduction, stabilization, and capping. Phytochemical analysis of the extract revealed that flavonoids, saponins, steroids, triterpenoids, and resins were present. The antibacterial activity of W. Formatted: Font: (Default) +Headings CS (Times New Roman), Complex Script Font: +Headings CS (Times New Roman) Formatted: Font: (Default) +Headings CS (Times New Roman), Complex Script Font: +Headings CS (Times New Roman) . bifurcata synthesised nanoparticles was evaluated against pathogenic bacteria. The ZnONPs antioxidant activity was assessed using DPPH assay. The in vitro cytotoxicity was assessed against prostate cancer PC3 cells. The wound healing potential was assessed by employing in vitro scratch assay and in vivo excision model in Wistar rats. Because of its environmentally benign production, low toxicity, and biocompatibility, ZnONPs have potential antibacterial, antioxidant, anticancer, and wound healing activities, indicating that they could be used in cancer treatment and wound management. Further study is required to examine the fundamental mechanisms and evaluate the safety and effectiveness of the test sample in clinical situations.